The Characteristics of Binary Spike-Time-Dependent Plasticity in HfO(2)-Based RRAM and Applications for Pattern Recognition - Zhou, Zheng (Nanoscale Res Lett, 2017)
A binary spike-time-dependent plasticity (STDP) protocol based on one resistive-switching random access memory (RRAM) device was proposed and experimentally demonstrated in the fabricated RRAM array. Based on the STDP protocol, a novel unsupervised online pattern recognition system including RRAM synapses and CMOS neurons is developed. Our simulations show that the system can efficiently compete the handwritten digits recognition task, which indicates the feasibility of using the RRAM-based binary STDP protocol in neuromorphic computing systems to obtain good performance.